Experimental and numerical investigation of the melting process and heat transfer characteristics of multiple phase change materials. (11th August 2020) - Li, Wei; Wang, Jun; Zhang, Xu; Liu, Xueling; Dong, Hongbiao
Summary: The melting and heat transfer characteristics of multiple phase change materials (PCMs) are investigated both experimentally and numerically. Multiple PCMs, which consist of three PCMs with different melting points, are filled into a rectangle‐shaped cavity to serve as heat storage unit. One side of the cavity is set as heating wall. The melting rate of multiple PCMs was recorded experimentally and compared with that of single PCM for different heating temperatures. A two‐dimensional mathematical model to describe the phase change heat transfer was developed and verified experimentally. The properties of multiple PCMs, including the effect of the melting point difference (combined type), thermal conductivity, and latent heat, on the heat transfer performance of the PCM were analyzed numerically. The results show that, the melting time decreases before it increases, with an increasing melting point difference for the multiple PCMs. In addition, the melting point decreases with increasing distance from the heating wall. Most of these types of multiple PCMs melt faster than the single PCM, and the multiple PCMs, with the melting point arranged as 322 K/313 K/304 K, has the shortest melting time in this study. The melting rate of the multiple PCMs, 322 K/313 K/304 K, accelerates faster than for the single PCM as the thermal conductivity, latent heat, and heating wall temperature increase. Finally, generalized results are obtained using a dimensionless analysis for both single and multiple PCMs.